2011
DOI: 10.1007/s11999-010-1728-3
|View full text |Cite
|
Sign up to set email alerts
|

Do First-generation Highly Crosslinked Polyethylenes Oxidize In Vivo?

Abstract: Background Highly crosslinked and thermally treated polyethylenes were clinically introduced to reduce wear and osteolysis. Although the crosslinking process improves the wear performance, it also introduces free radicals into the polymer that can subsequently oxidize. Thermal treatments have been implemented to reduce oxidation; however, the efficacy of these methods with regard to reducing in vivo oxidative degradation remains to be seen. Polyethylene oxidation is a concern because it can compromise the ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 28 publications
4
39
1
Order By: Relevance
“…In the other cases, namely remelted HXLPE subjected to aging alone, or to aging and cyclic loading, comparatively lower OIs were registered. Our results generally agree with previous retrieval studies that confirmed ex vivo stability loss and measurable oxidation levels for remelted HXLPE explants [9,15,16,22,24]. In this sense, Oral and colleagues recently demonstrated that absorbed squalene, a biological prooxidant, could initiate and accelerate oxidation in remelted crosslinked polyethylene [24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the other cases, namely remelted HXLPE subjected to aging alone, or to aging and cyclic loading, comparatively lower OIs were registered. Our results generally agree with previous retrieval studies that confirmed ex vivo stability loss and measurable oxidation levels for remelted HXLPE explants [9,15,16,22,24]. In this sense, Oral and colleagues recently demonstrated that absorbed squalene, a biological prooxidant, could initiate and accelerate oxidation in remelted crosslinked polyethylene [24].…”
Section: Discussionsupporting
confidence: 92%
“…However, retrieval studies have recently reported measurable oxidation levels in remelted HXLPE explants [8,15,22]. The mechanisms of in vivo oxidation of remelted HXLPE implants remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are indications that any type of UHMWPE that has been irradiated, including the two studied in the present paper, may show oxidation in vivo, which is known to be detrimental for the strength and the wear resistance [23]. Therefore the fact that only fresh UHMWPE specimens were tested may be considered a limitation of the study.…”
Section: Discussionmentioning
confidence: 91%
“…Oxidative degradation of some of the first generation of CLPE formulations has been considered a potential limiting factor for the long-term performance of THA [7,28]. During gamma irradiation (for crosslinking or for sterilization), free radicals formed in the PE molecular structure cause embrittlement through a cascading oxidation reaction [7].…”
Section: Introductionmentioning
confidence: 99%